Admissão de prova ilícita no âmbito do processo do trabalho - Oliveira, Stéfani Lorena Jácome (Universidade Federal Rural do Semi-Árido, 2017)
The use of unlawful evidence in the labor process has elicited relevant discussions in the face of the incessant search for real truth. In this context, it is considered necessary to ensure, as a corollary of the law, substantial access to justice. The right to the proof, in turn, is very important, because it consists in the ability to recreate in a process what happened in the factual world. It is known, however, that the Brazilian legal system imposes limits on the production of evidence in both judicial and administrative proceedings. To go beyond the limits of the right to proof means to turn a lawful evidence into an unlawful one. On the subject of the production of illicit evidence, the central question is whether or not it is admissible in the process, especially in the labor court, where the real truth gains preponderance in the face of the employee's hyposufficiency, including with regard to the production of evidence. In view of the above, as a constitutional fence for the admission of illicit evidence, it must be reinterpreted in the labor process, so as to privilege the real truth and to prestige a social function of the process? To deal with the theme, the method of deductive approach and the bibliographic research technique will be used, using sources of qualitative information. In the end, it is concluded that the admission of illegal evidence in the labor process is feasible, because, even in the face of the conflicts of principles, this posture is an important strategy to guarantee workers' rights.
Trabalho de Conclusão de Curso
Artigo Acadêmico
Keywords: Prova ilícita; Admissão; Princípio da verdade real; Unlawful evidence; Admission; Principle of real truth; CIENCIAS SOCIAIS APLICADAS::DIREITO